Major Choices: Students’ Personal Intelligence, Considerations When Choosing a Major, and Academic Success - Kateryna Sylaska; John D. Mayer (Journal of Intelligence)
A student’s choice of major is influenced by their parents and peers, as well as by the quality of the college department that offers the major and by broader cultural and economic issues. The student’s own personality, including their ability to reason about themselves and their interests, also contributes to the choice and its outcomes. In a preliminary study, we developed a Choice of Major Scale that depicts key aspects of students’ consideration of their major. Then, across three studies (Ns = 304, 466, and 492), we examined the students’ personal intelligence, defined as their capacity to reason about their own and other people’s personalities, as well as a Choice of Major Scale, and the relation of those variables to important academic outcomes. The results depicted a pattern that the students who better understood personality and were more engaged in choosing a major, compared to others, considered more majors initially, chose a major more quickly, and exhibited better academic outcomes subsequently.